Custom-designed wireless mote performance analysis in diverse node placement and antenna positioning scenarios for agricultural monitoring. (2017) - Viswanathan, Vijayaragavan; Narayanan, Ram Prasadh; Aslam, C. Ahamed; Anoop, R.S.; Mahalakshmi, V.J.
Objective of this work is to analyse various mote parameters, under different deployment and antenna positioning scenarios. The nodes were deployed and tested for its communication and sensing on the surface, under the ground and also in a hybrid environment. The results suggest that communication medium (underground and over-the-surface deployment) and the mote's antenna positioning, have considerable implications on received signal strength (RSS), packet delivery ratio (PDR) and signal attenuation. This research work has analysed the effect of transmission signal strength, packet loss and RSS, at different deployment and antenna positioning scenarios, taking into consideration, the power supply and other environmental parameters. The feasibility of implementing a wireless under-ground sensor network (WUSN) for agricultural monitoring is also studied.